2020
DOI: 10.1121/10.0002667
|View full text |Cite
|
Sign up to set email alerts
|

Noise annoyance during COVID-19 lockdown: A research of public opinion before and during the pandemic

Abstract: Strict lockdown strategies to stop the spread of COVID-19 have caused a decrease in environmental noise levels and introduced new noise conditions in dwellings. The present study has investigated the impact of the forced lockdown in Turkey on noise annoyances due to traffic, neighbors, and personal dwellings, as well as the concern of being heard by neighbors, and overall dwelling satisfaction in an online questionnaire. The stress and anxiety levels of respondents were also investigated. The survey obtained 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…However, the environmental noise-related issues were not the only concern during lockdown because a significant percentage of the population may also have faced anxieties and higher-stress levels while being confined to their homes in those highly uncertain times which indirectly affected people and their perception of the environment. 22 In fact, for people living near busy areas who were accustomed to a constant exposure to roadside noise were suddenly forced to live in a completely different acoustic environment which was much quieter, this may well have also caused mental-health issues arising out of feelings of confusion or loneliness.…”
Section: Environmental Noise Perception Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the environmental noise-related issues were not the only concern during lockdown because a significant percentage of the population may also have faced anxieties and higher-stress levels while being confined to their homes in those highly uncertain times which indirectly affected people and their perception of the environment. 22 In fact, for people living near busy areas who were accustomed to a constant exposure to roadside noise were suddenly forced to live in a completely different acoustic environment which was much quieter, this may well have also caused mental-health issues arising out of feelings of confusion or loneliness.…”
Section: Environmental Noise Perception Surveymentioning
confidence: 99%
“… 21 A survey of over 1000 participants across Turkey revealed that annoyance due to outdoor noise reduced considerably during the lockdown, particularly for busy residential neighborhoods, and it positively correlated with stress and anxiety levels. 22 …”
Section: Introductionmentioning
confidence: 99%
“…A general reduction of outdoor noise levels has been observed due to contingency measures in several countries [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] . In terms of noise annoyance, studies have showed a persistence [9] or reduction [10] , [11] , [12] in annoyance due to outdoor noise, a reduction [11] , persistence [10] or increase [9] , [12] in annoyance towards neighbourś noise, and an increase in annoyance due to noise from onés own dwelling [9] , [10] during the lockdown compared to before.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining documents directly related to acoustics was relatively difficult, as issues on the acoustics (noise levels) and its impact on COVID-19 have yet to be fully explored. Majorly, the documents addressed issues of noise pollution and its impact on sleep patterns as well as noise and occupant comfort (Şentop Dümen and Şaher, 2020; Díaz et al , 2021). The studies attempted to establish noise levels as a hindrance to the general health and well-being of confined occupants (Salamone et al , 2021) and its impact on concentration (Lee and Jeong, 2021), sleep patterns and general comfort (Morano et al , 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%